2015
DOI: 10.3892/ijmm.2015.2162
|View full text |Cite|
|
Sign up to set email alerts
|

NLRP3 inflammasome is responsible for Hantavirus inducing interleukin-1β in THP-1 cells

Abstract: Persistent high fever is one typical clinical symptom of hemorrhagic fever with renal syndrome (HFRS) and circulating interleukin-1β (IL-1β) is elevated throughout HFRS. The mechanisms responsible for viral induction of IL-1β secretion are unknown. In the present study, Hantaan virus (HTNV) induced the secretion of IL-1β in the human monocytic cell line THP-1. Induction of IL-1β by HTNV relies on the activation of caspase-1. Small hairpin RNA knockdown in HTNV-infected THP-1 cells indicated that nucleotide-bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…Cleaved caspase-1 modulates the maturation of pro-inflammatory cytokines, including IL-1β and IL-18 ( 43 ). Previously, NLRP3 caused renal injury has been reported ( 44 ). We found that TXNIP and NLRP3 signaling pathway was upregulated for LPS treatment, followed by ASC and caspase-1 cleavage increase, which was in line with the inflammation response.…”
Section: Discussionmentioning
confidence: 98%
“…Cleaved caspase-1 modulates the maturation of pro-inflammatory cytokines, including IL-1β and IL-18 ( 43 ). Previously, NLRP3 caused renal injury has been reported ( 44 ). We found that TXNIP and NLRP3 signaling pathway was upregulated for LPS treatment, followed by ASC and caspase-1 cleavage increase, which was in line with the inflammation response.…”
Section: Discussionmentioning
confidence: 98%
“…The improved plaque formation test is dependent on the low pH-induced cytopathic effects of hantavirus but is time-consuming and has low reproducibility. The most widely adopted approach to test hantavirus titers (especially for HTNV) is the TCID50 (50% tissue culture infective dose) calculation using ELISA as previously reported by our group (Xu et al, 2002; Cheng et al, 2014; Jiang et al, 2015; Ye et al, 2015a,b; Ying et al, 2016); however, virus propagation in Vero E6 cells takes at least 10 days. All the reported detective measurements have insurmountably objective drawbacks, such as high demanding experimental conditions for qRT-PCR and expensive apparatus and labware for FCM, which limits their applicability (Wan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the NLRP3 inflammasome is capable of recognizing RVFV and HNTV infection (75,76). RVFV alone could barely promote the activation of the NLRP3 inflammasome.…”
Section: Pyroptosis In Anti-sftsv Immunitymentioning
confidence: 99%